Functionalization of MXene-based nanomaterials for the treatment of micropollutants in aquatic system: A review. (15th May 2022) - Velusamy, Karthik; Chellam, PadmanabanVelayudhaperumal; Kumar, P. Senthil; Venkatachalam, Jeyamanikandan; Periyasamy, Selvakumar; Saravanan, R.
Abstract: The increased industrialization and urbanization generate a larger quantity of effluent that is discharged into the environment regularly. Based on the effluent composition produced from various industries, the number of hazardous substances such as heavy metals, hydrocarbons, volatile organic compounds, organic chemicals, microorganisms introduced into the aquatic systems vary. The conventional wastewater treatment systems do not meet the effluent standards before discharge and require a different treatment system before reuse. Adsorption is an eco-friendly technique that uses selective adsorbents to remove hazardous pollutants even at microscale levels. MXene, a 2-Dimensional nanomaterial with resplendent properties like conductivity, hydrophilicity, stability, and functionalized surface characteristics, is found as a potential candidate for pollutant removal systems. This review discusses the fabrication, characterization, and application of MXene based nanoparticles to remove many pollutants in water treatment systems. The improvement in surface properties and adsorption capacity of MXene based NPs, when modified using different modification agents, has also been discussed. Their feasibility in terms of economic and environmental aspects has been evaluated to understand their scope for practical application in large-scale industries. The challenges towards the synthesis and toxicity's importance have been discussed, with the appropriate recommendations. Highlights: Potential of nanoparticles as a catalyst against micropollutants. Strategies in the preparation and characterization of specific MXenes. Challenges and opportunities towards the removal of metal ions by MXenes. Possibilities on the surface modified MXenes for the adsorption of pollutants.